Analisis Sistem Saraf Pusat Otak pada Mamalia Mencit (Mus musculus) - Estianti Estianti; Keisya Salsabila; Layya Nadira; Nesariza Maharani; Jodion Siburian; Afreni Hamidah; Desfaur Natalia (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The mouse (Mus musculus) is a widely used animal model in neuroscience research due to the structural and functional similarities of its nervous system to that of humans. However, information regarding the structure and function of the mouse central nervous system remains scattered across various publications, necessitating a synthesis to provide a comprehensive overview. This study aims to synthesize research findings on the anatomical structure and function of the mouse brain's central nervous system based on a literature review. The review covered scientific articles published between 2019 and 2024, retrieved via Google Scholar and Publish or Perish. Articles were selected based on inclusion criteria specifically, research addressing the anatomy, neuroanatomy, physiology, or function of the central nervous system in Mus musculus while irrelevant or duplicate articles, as well as those unavailable in full-text format, were excluded from the analysis. All articles meeting the criteria underwent a descriptive-comparative analysis to identify similarities, differences, and trends in findings. The synthesis reveals a consistent consensus that the cerebrum, cerebellum, brainstem, and limbic system are the primary components of the central nervous system, integrating to regulate sensory, motor, cognitive, and behavioral functions. The six-layered cerebral cortex plays a dominant role in information processing, whereas the hippocampus is the structure most frequently associated with mechanisms of memory formation, learning, and stress responses. Glutamate and GABA were identified as key neurotransmitters maintaining the balance between excitatory and inhibitory activity, while dopamine and serotonin contribute to the regulation of behavior, motivation, and emotional function. This synthesis demonstrates that the integration of neuroanatomical structures with neurotransmission mechanisms forms the fundamental basis of central nervous system function in mice, thereby serving as a conceptual framework for selecting animal models in neurological research and the development of studies on neurodegenerative diseases.